2007
DOI: 10.2136/sssaj2006.0137
|View full text |Cite
|
Sign up to set email alerts
|

Soil Phosphorus and Vegetation Influence on Wetland Phosphorus Release after Simulated Drought

Abstract: Phosphorus enrichment of marsh soils can act as an internal source of nutrients to the water column, continuing to drive existing wetland eutrophic conditions even after external sources have been terminated. The goal of this study were to determine the effects of soil P concentration and flood intolerant vegetation presence on initial (1–10 d) and extended (10–38 d) P release rates from the soils after reflooding. Intact soil cores were collected from P enriched and unenriched areas of the Blue Cypress Marsh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 43 publications
7
44
1
1
Order By: Relevance
“…TP in peat-burned areas was 47%, 136%, 687% and 36% significantly higher than that in surface-burned areas, respectively. Bostic and White (2007) indicated that phosphorus enrichment of marsh soils can act as an internal source of nutrients to the water column and drive existing wetland eutrophic conditions. Steward and Ornes (1975) found a strong nutrient relationship in sawgrass re-growth after fire which differed considerably from sawgrass in non-burned areas.…”
Section: Discussionmentioning
confidence: 99%
“…TP in peat-burned areas was 47%, 136%, 687% and 36% significantly higher than that in surface-burned areas, respectively. Bostic and White (2007) indicated that phosphorus enrichment of marsh soils can act as an internal source of nutrients to the water column and drive existing wetland eutrophic conditions. Steward and Ornes (1975) found a strong nutrient relationship in sawgrass re-growth after fire which differed considerably from sawgrass in non-burned areas.…”
Section: Discussionmentioning
confidence: 99%
“…The opposing trends observed in the spatial distributions of N and P within the tree islands resulted in a strong gradient in soil N:P ratios from head to tail of the TI's. Given the high rainfall in the Everglades area (German, 2000), the elevated topography of the TI's, the low P concentration in the slough, and an Everglades-wide geochemistry that favours P remobilization from P enriched to P unenriched areas (Bostic & White, 2007;Bostic et al, 2010) a strong mechanism of phosphorus retention must be in place for such a strong concentration gradient to be maintained between hammock, surrounding swamp forest, and adjacent marsh. The ability of wetland soil to retain P depends on the physico-chemical characteristics of the sediment and overlying water.…”
Section: Nutrient Statusmentioning
confidence: 99%
“…In addition, in wetlands that are unsaturated during drawdown events, soil oxidation is increased and reflooding may subsequently mobilize P (Bostic and White 2006). Episodic drops in water levels can increase organic matter decomposition, potentially increasing P loading to the water column on reflooding (Watts 2000;DeBusk and Reddy 2003).…”
Section: Background and Motivationmentioning
confidence: 99%